Hybridization and polyploidization within the Chenopodium album aggregate analysed by means of cytological and molecular markers - Mandák, Bohumil; Krak, Karol; Vít, Petr; Lomonosova, Maria N; Belyayev, Alexander; Habibi, Farzaneh; Wang, Lei; Douda, Jan; Štorchová, Helena (Molecular phylogenetics and evolution, 2018)
Hybridization and polyploidization represent an important speciation mechanism in the diploid-polyploid complex of the Chenopodium album aggregate. In the present study we successfully reconstructed the evolutionary histories of the majority of Eurasian representatives of the C. album aggregate, resulting in the most comprehensive phylogenetic analysis of this taxonomically intricate group of species to date. We applied a combination of classical karyology for precise chromosome number determination, genomic in-situ hybridization for the determination of genomic composition, flow cytometry for the estimation of genome size and sequencing of plastid (cpDNA) and nuclear (ribosomal internal transcribed spacer - ITS and the introns of the FLOWERING LOCUS T LIKE genes - FTL) markers for a phylogenetic reconstruction and the identification of parental genomes in polyploid taxa. The FTL markers identified eight well supported evolutionary lineages. Five of them include at least one diploid species, and the remaining three comprise solely the subgenomes of polyploids that probably represent extinct or unknown diploid taxa. The existence of eight basic diploid lineages explains the origin of seven Eurasian polyploid groups and brings evidence of a nearly unlimited number of subgenomic combinations. The supposed promiscuity generated new species wherever different diploid lineages met each other and gave rise to tetraploid species or whenever they met other tetraploid species to produce hexaploid species throughout their evolutionary history. Finally, we unravelled a surprisingly simple scheme of polyploid species formation within the C. album aggregate. We determined seven groups of polyploid species differing in their origin in either Eurasia or Africa and convincingly demonstrated that (1) all Chenopodium polyploid species under study are of allopolyploid origin, (2) there are eight major monophyletic evolutionary lineages represented by extant or extinct/unknown diploid taxa, (3) those monophyletic lineages represent individual subgenomes, (4) hybridization among the lineages created seven subgenomic combinations of polyploid taxa, (5) taxa represented by particular subgenome combinations were further subjected to diversification, and (6) the majority of species are relatively young, not exceeding the age of the Quaternary period.
Keywords: Hybridization, Genetic; Chenopodium album; nrDNA ITS; Genetic Loci; sekvence nukleotidů; Base Sequence; Polyploidy; fylogeneze; Chenopodium; Allopolyploidy; polyploidie; Chromosomes, Plant; Evolution, Molecular; Genome Size; tetraploidie; Phylogeny; cpDNA; Genetic Markers; genetické markery; genetické lokusy; chromozomy rostlin; Tetraploidy; délka genomu; FTL genes; molekulární evoluce; hybridizace genetická; Hybridization